Fetal Spinal Cord Tissue in Mini-Guidance Channels Promotes Longitudinal Axonal Growth after Grafting into Hemisected Adult Rat Spinal Cords. Issue 4 (1999) - Bamber, Norman I.; Li, Huaying; Aebischer, Patrick; Xu, Xiao Ming
Abstract : Solid fetal spinal cord (FSC) tissue, seeded into semipermeable mini-guidance channels, was tested for the ability to promote axonal growth across the gap created by a midthoracic (T8) hemisection in adult rats. Fetal thoracic spinal cords, at embryonic days 13 to 15, were harvested and gently aspirated into mini-guidance channels (1.25 mm in diameter and 3.0 mm in length). Care was taken to maintain the rostro-caudal orientation of the FSC. In control rats, the FSC-channel congraft struct was exposed to 5 freeze/thaw cycles to produce non-viable grafts before implantation into the hemisected cord. All cases revealed intact tissue cables of various diameters spanning the rostro-caudal extent of the lesion cavity, with integration of host-graft tissues at both interfaces. Immunofluorescence results indicated that numerous neurofilament-positive axons were present within the FSC tissue cable. Double-labeling of a subpopulation of these axons with calcitonin generelated peptide indicated their peripheral nervous system (PNS) origin. Descending serotonergic and noradrenergic axons were found in the proximity of the rostral host-graft interface, but were not observed to grow into the FSC-graft. Anterograde tracing of propriospinal axons with Phaseolus vulgaris-leucoagglutinin demonstrated that axons had regenerated into the FSC-graft and had traveled longitudinally to the distal end of the channel. Few axons were observed to cross the distal host-graft interface to enter the host spinal cord. Cross-sectional analysis at the midpoint of the tissue cable stained with toluidine blue demonstrated a significant increase (P<0.01) in myelinated axons in viable FSC grafts (1455±663, mean±S.E.M.; n=6) versus freeze-thaw control grafts (155±50; n=5). In addition to the myelinated axons, many unmyelinated axons were observed in the tissue cable at the electron microscopic level. Areas resembling the PNS with typical Schwann cells, as well as those resembling the central nervous system with neurons and central neuropil, were also seen. In freeze-thaw control grafts, neither viable neurons nor central neuropil were observed. Retrograde tracing with Fast Blue and Diamidino Yellow demonstrated that neurons within the FSC graft extended axons into the host spinal cord at least for 2 mm from both the rostral and caudal host-graft interfaces. We conclude that viable FSC grafts within semipermeable guidance channels may serve both as a permissive bridge for longitudinally directed axonal growth and a potential relay for conveying information across a lesion site in the adult rat spinal cord.